2011
DOI: 10.21837/pmjournal.v9.i2.85
|View full text |Cite
|
Sign up to set email alerts
|

Solid Waste Generation Characteristics: The Malaysian Local Authorities' Outlook

Abstract: The large and increasing amounts of municipal solid waste (MSW) generated each year in several industrialised countries have raised concerns on the economic viability and environmental acceptability of the current generation activities. The planning of an optimal regional waste management strategy requires a reliable tool for predicting the amount and the corresponding composition of MSW likely to be produced. Furthermore, for integrated solid waste management, direct and indirect participation of local govern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The total score of this construct is then computed in order to interpret the raw scores in a more manageable way. Subsequently, the summated scores are further segregated into three categories, namely Low (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), Moderate (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44), and High (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60). To conclude, the higher the score, the higher the injunctive norm towards intention to practise solid waste segregation-at-source.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total score of this construct is then computed in order to interpret the raw scores in a more manageable way. Subsequently, the summated scores are further segregated into three categories, namely Low (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), Moderate (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44), and High (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60). To conclude, the higher the score, the higher the injunctive norm towards intention to practise solid waste segregation-at-source.…”
Section: Methodsmentioning
confidence: 99%
“…More terribly, it is reported that there is about 60 per cent of the 32 million Malaysians fail to throw their garbage into rubbish bins [22]. Therefore, Malaysian households should cultivate the intention to practise solid waste segregation-at-source immediately for a better and ideal living environment for the next generation in the future [23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This would ensure that the waste-dumping area is kept hidden, away from public view while accessible by waste collecting trucks. This is to ensure a better living environment for the nearby residents (Abu Eusuf et al, 2011) METHODOLOGY This research will be using multiple case study method where observation and dichotomous close-ended questionnaire with the residents will be done in parallel. Interpretivism paradigm was chosen as the research method as it involves researchers and the residents to interpret elements.…”
Section: Improper Service Areamentioning
confidence: 99%
“…According to Sachs (2015), acting and conducting activities to safeguard the environment is part of environmental protection. Consequently, the Malaysian government has raised concerns regarding environmental protection and the importance of waste disposal management due to a lack of landfill space, increased waste management costs, and inefficient recycling management (Eusuf et al, 2011). Moreover, Mokhtar et al (2013) claimed that Malaysia collected 33,000 tons of waste each day in 2013, an increased volume from 19,000 tons in 2005, thereby raising the cost of waste management with a further absence of a proper mechanism that addresses the poor recycling of domestic waste.…”
Section: Introductionmentioning
confidence: 99%